Effects of porosity in a model of corrosion and passive layer growth - F.D.A. Aarão Reis (Condensed Matter Physics, 2017)
We introduce a stochastic lattice model to investigate the effects of pore formation in a passive layer grown with products of metal corrosion. It considers that an anionic species diffuses across that layer and reacts at the corrosion front (metal-oxide interface), producing a random distribution of compact regions and large pores, respectively represented by O (oxide) and P (pore) sites. O sites are assumed to have very small pores, so that the fraction Φ of P sites is an estimate of the porosity, and the ratio between anion diffusion coefficients in those regions is Dr < 1. Simulation results without the large pores (Φ = 0) are similar to those of a formerly studied model of corrosion and passivation and are explained by a scaling approach. If Φ > 0 and Dr 1, significant changes are observed in passive layer growth and corrosion front roughness. For small Φ, a slowdown of the growth rate is observed, which is interpreted as a consequence of the confinement of anions in isolated pores for long times. However, the presence of large pores near the corrosion front increases the frequency of reactions at those regions, which leads to an increase in the roughness of that front. This model may be a first step to represent defects in a passive layer which favor pitting corrosion. Представлено стохастичну ґраткову модель для вивчення ефектiв формування пор у пасивному шарi, який вирощується з продуктами корозiї металу. Вважається, що анiони дифундують через цей шар i реагують на корозiйнiй межi (межi роздiлу металу та оксиду), утворюючи випадковий розподiл компактних областей i великих пор, якi вiдповiдають вузлам видiв О (оксид) i Р (пора). Припускається, що вузли виду О мають дуже малi пори, тобто частка Φ вузлiв виду P приблизно вiдповiдає пористостi, а спiввiдношення коефiцiєнтiв дифузiї анiонiв у цих областях Dr < 1. Результати моделювання для випадку вiдсутностi великих пор (Φ = 0) подiбнi до результатiв для попередньої моделi корозiї та пасивацiї i пояснюються масштабним пiдходом. При Φ > 0 i Dr 1 спостерiгаються суттєвi змiни в ростi пасивного шару i жорсткостi корозiйної межi. Для малих Φ зауважено сповiльнення швидкостi росту, яке можна пояснити тривалим обмеженням руху анiонiв в iзольованих порах. Однак присутнiсть великих пор поблизу корозiйної межi збiльшує частоту реакцiй в цих областях, приводячи до збiльшення жорсткостi межi. Дану модель можна розглядати як перший крок при описi дефектiв у пасивному шарi, якi сприяють герметичнiй корозiї.